Individualization and Communality in the Context of Vocational Training - Kanapickaitė, Jolanta (Pedagogika, 2013)
This article discloses individualization / communality in the studies process of designers, photographers-technologists, engineers, marketing, communications and health care specialists. The research was done in 2009–2012 years of studies in Vilnius college, Kaunas college, International school of law and business, Vilnius Gediminas technical university, Vilnius Art academy, Vilnius college of technologies and design studies programs: marketing, advertisement, marketing and management, creative industries, visual communication, general practice nursing, biomedical diagnostics, hygienic and decorative cosmetics, physical therapy, graphic design, interior design, interactive design and photography technologies, building services, construction, geodesy and cadaster, heating energetic. The aim of this article is to disclose individualization / communality in the vocational studies process of designers-photographers technologists, engineers, marketing, and communication and health care specialists. Research data showed what communality the general direction of engineers’ and health care specialist vocational is training. And the statistical data analysis revealed the following: artist and manager named individualization as a general direction of vocational training.